PDGFs and their receptors in vascular stem/progenitor cells: Functions and therapeutic potential in retinal vasculopathy. (August 2018) - Lu, Weisi; Li, Xuri
Abstract: Vascular stem/progenitor cells (VSCs) include endothelial progenitor cells, smooth muscle progenitor cells, pericytes, and mesenchymal stem cells. VSCs can produce functional and mature vascular cells required to build blood vessels. VSCs therefore play critical roles in vascular repair and regeneration, particularly, in various retinal vasculopathies, in which vascular defects are a devastating pathology. The platelet-derived growth factors (PDGFs) and their receptors (PDGFRs) are important regulators of numerous physiological events and diseases, and they play key roles in regulating the formation and function of blood vessels. A better understanding of the effects of PDGFs/PDGFRs on VSCs and a thorough elucidation of their therapeutic potential in the treatment of retinal vasculopathies are critical for both basic and translational research and may lead to better therapies for human vascular diseases.